Культурная идентичность в процессе русско-польского перевода - Jóźwiak, Jolanta (Studia Rossica Posnaniensia, 2020)
The article deals with the issue of transferring intertextual cultural elements in the process of translation from Russian into Polish. The material for analysis is the fragments of the novel The Black City by Boris Akunin and its translation into Polish by Aleksandra Okuniewska-Stronka. The aim of this article is to present and evaluate the results of transferring cultural connotations and intertextual references from one culture to another. Cultural elements play a significant role in the process of the reception of the text and its translation both by the readers of the original text ‒ native language users – and by the recipients of the translated variant, belonging to a different culture. The comparison of source units and translated target units shows how different the associative circles arising in the process of text reception are. The analysis leads to the conclusion that taking into account the associative and intertextual potential of language units in translation is a very complex process. It requires a double cultural competence from the translator, and involves not only the interpretation of language signs in terms of their cultural code, but also the assessment of the interpretative abilities and capabilities of the recipients.